Cutaneous lymphoma misdiagnosed as chronic lymphadenitis. Issue 6 (22nd April 2015) - Munteanu, Mircea; Mohor, Georgiana S; Baderca, Flavia; Solovan, Caius
Abstract: Cutaneous lymphomas (CLs) represent a group of lymphoproliferative disorders that can be difficult to diagnose in the early stage because they could mimic many benign inflammatory dermatoses (chronic eczema, bullous dermatosis, idiopathic erythroderma, psoriasis, lymphadenitis). Primary cutaneous B‐cell lymphomas are a unique and controversial group of skin lymphomas characterised by the absence of extracutaneous manifestations at diagnosis. We present the case of a 60‐year‐old man with 7‐month history of a growing inguinal mass/tumour, which was misdiagnosed as inguinal chronic lymphadenitis. Recognition of the correct entity, primary cutaneous diffuse large B‐cell lymphoma leg type, led to an appropriate therapeutic strategy, knowing that these types of tumours behave more aggressively than other types of primary cutaneous B‐cell lymphomas. The patient was discharged with rituximab + chemotherapy indication and favourable outcome. The aim of the presentation is to describe these common skin manifestations, however seen in a primary cutaneous B‐cell lymphoma, which underlines the necessity of rigorous monitoring/long‐term follow‐up as well as exhaustive histopathological analysis for the diagnosis.